In-Vitro Conservation of Sugarcane Germplasm - Ikram, Rabia; Erum, Shazia; Javed, Hina; Zaman, Shah; Shahid Khan; Muhammad , Aish; Kanwal, Saima (Asian Journal of Agriculture and Rural Development, 2014)
Lack of in vitro multiplication procedure has long been a serious problem in sugarcane breeding programs. This problem has been solved to maximum extent by In Vitro propagation. In the present study, 6 genotypes of sugarcane (SC 06, SC 04, SC 25, SC 11, SC 13 and SC 30) was acquired & excised for apical and sub apical parts (eyes/ lateral buds). The explants were surface sterilized with Clorox (70% +100%, 20 & 10 min). Results showed that highest survival % was achieved with apical buds (66%) as compared to lateral buds (33%). In addition, effect of different concentrations of rooting media (NAA, 5% Sucrose and 6% Sucrose) and shooting media (GA3, 0.1mg/, Kinetin, 0.1mg/L and BAP 0.1mg/L, Kinetin 0.1mg/L,GA3 0.1mg/L, NAA 0.1mg/L) was studied. Synergistic response was observed on the growth of plant with hormone consortia. Significant differences were observed in No. of roots, shoot length @ No. of shoots at all tested treatments. Highest No. of roots recorded for SC 30 at with 6% Sucrose. Highest No. of shoots was recorded for SC 04 with GA3 @ 0.1mg/L and highest shoot length for SC 06 at 0.1mg/ L of Kinetin.